Paper and electronic versions of HM-PRO, a novel patient-reported outcome measure for hematology: an equivalence study. (30th April 2019) - Goswami, Pushpendra; Oliva, Esther N; Ionova, Tatyana; Else, Roger; Kell, Jonathan; Fielding, Adele K; Jennings, Daniel M; Karakantza, Marina; Al-Ismail, Saad; Lyness, Jack; Collins, Graham P; McConnell, Stewart; et al.
Aim: To determine measurement equivalence of paper and electronic application of the hematological malignancy-patient-reported outcome (HM-PRO), a specific measure for the evaluation of patient-reported outcomes in HMs.Patients & methods: Following International Society of Pharmacoeconomics and Outcomes Research ePRO Good Research Practice Task Force guidelines, a total of 193 adult patients with different HMs were recruited into a multicenter prospective study. The paper and the electronic version of the instrument were completed in the outpatient clinics in a randomized crossover design with a 30 min time interval to minimize the learning effect. Those who completed the paper version first, completed the electronic version after 30 min and vice versa. Instrument version and order effects were tested on total score of the two parts of the HM-PRO (Part A: quality of life and Part B: signs & symptoms) in a two-way ANOVA with patients as random effects. Intraclass correlation coefficients (95% CI) and Spearman's rank correlation coefficients were used to evaluate test–retest reliability and reproducibility. The effects of instrument version and order were tested on total score of the two parts of HM-PRO.Results: The questionnaire version and administration order effects were not significant at the 5% level. There were no interactions found between these two factors for HM-PRO (Part A [quality of life]; p = 0.95); and (part B [signs and symptoms]; p = 0.72]. Spearman's rank correlation coefficients were greater than 0.9, and intraclass correlation coefficients ranged from 0.94 to 0.98; furthermore, the scores were not statistically different between the two versions, showing acceptable reliability indexes. Noteworthy, the difference between the completion time for both paper (mean = 6:38 min) and electronic version (mean = 7:29 min) was not statistically significant (n = 100; p = 0.11). Patients did not report any difficulty in completing the electronic version during cognitive interviews and were able to understand and respond spontaneously.Conclusion: Measurement equivalence has been demonstrated for the paper and electronic application of the HM-PRO.